THE ROLE OF SERVANT LEADERSHIP OF THE PRINCIPAL IN INCREASING STAKEHOLDER SATISFACTION AT SMP YPM TENGGARONG SEBERANG - Maysyaroh, Binti Syafaati; Muadin, Akhmad (Pimpinan Cabang Muhammadiyah Kramat Jati, 2023)
This study aims to determine the implementation of the principal's Servant Leadership role in increasing stakeholder satisfaction at YPM Tenggarong Seberang Junior High School. This research uses a qualitative approach with a case study method. The research subjects in this study were principals, teachers and student guardians, and students. Data collection techniques using interviews, observation and documentation. The results showed that servant leadership applied at SMP YPM Tenggarong Seberang was oriented towards increasing stakeholder satisfaction. There are several characteristics that must be possessed by a principal in carrying out his leadership